Aberrant origin of right vertebral artery from right common carotid artery in a right‐sided aortic arch. Issue 3 (7th January 2022) - Verma, Mansi; Pandey, Niraj Nirmal; Kumar, Sanjeev; Ramakrishnan, Sivasubramanian
Abstract: We present a case of a 2‐year‐old girl with incidentally detected aberrant origin of right vertebral artery from right common carotid artery in a right‐sided aortic arch. The case highlights the role of computed tomography angiography in detecting anomalies of the aortic arch and arch vessels in the setting of complex congenital heart diseases while also discussing the potential clinical implications.